Green Digital Finance As A Way Of Boosting Sustainable Development:case Of Asian Pacific Region - Lallouche Ghania (جامعة الوادي University Of Eloued, 2024)
This research aimed to highlight the importance of green digital finance as a way of supporting sustainabledevelopment by focusing on Asia pacific area. The research concluded that green digital finance could be a vital support of sustainable development in the area in question. It contains very good digital services that can contribute in promoting green digital finance, by encouraging a big part population in the world to participate in financing green infrastructures, if they intensify their usage of digital payment, and then the banking system in the region can use their money to finance green development.
Keywords: green finance; financial technology; sustainable development; digital green finance; Asian pacific area